النظرية الدلالية لتفسير سورة النبأ في كتاب تفسير الجلالين / The Semantic Theory to The Interpretation of Surah An-Naba' in Tafsir Jalalain - Marwah Limpo (Diwan : Jurnal Bahasa dan Sastra Arab, 2021)
هذا البحث يحلّل أنواع المعنى وعلاقة  المعنى الذي يستخدمها المؤلّف لتفسير الكلمة أو اللفظ في سورة النبأ, ويهدف إلى معرفة أوجه القصور في اختيار كل الكلمة التفسيرية.هذا البحث بحث مكتبي ونوعه بحث وصفي نوعي وتحليله تحليل علم الدلالة، وأما مصدر البيانات الرئيسيىة فهو كتاب تفسير الجلالين، وأما البيانات الثانوية فهي مقالات وكتب دلالية. نتيجة هذا البحث تشير إلى أن أوجه القصور في كتاب تفسير الجلالين تتمثلت في نوع المعنى الذي يستخدمه المؤلّف عند تفسير كل كلمة أو لفظ في سورة النبأ. وأما نوع المعنى المستخدم على الأغلبية فهو المعنى الإشاري أي المعنى الذي يتعلق على شيء الذي يشير إلى الكلمة أو الجملة.  ولكن في الواقع, ذلك المعنى له  العديد من أوجه القصور، منها يملك أحيانا الإشارات الأخري التي تمكن المستخدمة في تفسير الكلمة أو اللفظ. ولكن في هذا الحال ، كان  المؤلّف يستخدم إحدى من كلمة إشارية (المشار إليه) فقط لتفسير كل الكلمة أو اللفظ في الآية. ومن الممكن هناك كلمة إشارية أخرى يستخدمها المفسر بعده لتفسير الآيات. وأما علاقة المعنى السائد فهي  علاقة مرادفة لأن عدة كلمات في السورة يتم تفسيرها بكلمات أخرى  لها  نفس المعنى.الكلمات المفتاحية: النظريةالدلالية; تفسير الجلالين; سورة النبأAbstract:This study analyzes the types of meanings and meaning relations used to interpret each word or lafadz in Surah an-Naba’ to know the deficiencies of the Jalalain commentary book on each choice of words used as interpretive words. This research uses descriptive qualitative and employs library research for the data collection method. Moreover, the data analysis applies semantic analysis. The primary data is in the form of the Jalalain commentary book, and the secondary data is in the form of articles and semantic books. The results showed that the shortcomings were found in the type of meaning used by the author in interpreting each word or lafadz in surah an-Naba’. The dominant meaning used in interpreting is referential meaning, which is a meaning that depends on something/a reference pointed to by a word or sentence. However, in this case it turns out that the referential meaning has several drawbacks, sometimes the meaning has several reference words. But only one-word reference is used by the Mufassir(interpreter) to interpret each word or lafadz in the verse to allow for other references that interpreters can use to interpret the verse. The dominant interpretive word/pronunciation used is the synonym relationship. Hence, there are many words or lafadz have similarity in meaning or one meaning.